Prenatal diagnosis of hemoglobin Bart's hydrops fetalis by HPLC analysis of hemoglobin in fetal blood samples - Sanguansermsri T. (2014)
Since HbF and HbA are not found in fetuses with Hb Bart's hydrops fetalis the feasibility of prenatal diagnosis of homozygous α-thalassemia 1 by fetal hemoglobin typing was examined. Blood samples were obtained from fetuses at 18 to 22 weeks of gestation by cordocentesis in 32 pregnant women at risk of having a child with homozygous α-thalassemia 1 (α-thal-1). The samples were analyzed by a PCR-based method for the diagnosis of α-thal-1 (SEA type) and the proportion of hemoglobin fractions were determined by automated HPLC. DNA analysis showed that 8 of the 32 fetuses were homozygotes for α-thal-1, 17 were heterozygous for α-thal-1 (α-thal-1 trait), and a normal complement of four α-globin genes was found in 7 cases. The Hb typing in fetuses with homozygous α-thal-1 showed a peak of unbound Hb (Hb Bart's and Hb Portland) and no HbF, HbA and HbA2. The α-thal-1 trait chromatograms showed unbound Hb, pre HbF, HbF and HbA peaks. The chromatogram of normal fetuses showed HbF and HbA peaks without HbA2. In these cases the HbA proportion is between 3% and 10% with no apparent differences between the 18th and 22nd week of gestation. As the analysis of fetal Hb types by HPLC is facile and speedy and the results correspond with those obtained by DNA analysis, fetal Hb typing by automated HPLC is a convenient prenatal diagnostic method for homozygous α-thal-1. The method is recommended for prenatal diagnosis in populations with a high frequency of α-thal-1.